HUBUNGAN TINGKAT AKTIVITAS FISIK, DENGAN STRESS,DEPRESI DAN KECEMASAN SISWA REMAJA USIA 17– 19 TAHUN DI SMA AL-ISLAM KRIAN - Ramadhan, Roihan; Pudjijuniarto, Pudjijuniarto; Yuliastrid, Dita; Irawan, Roy Januardi (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Physical activity plays an important role in adolescents' mental health. Increased activity can help reduce levels of stress, depression, and anxiety. This study aims to analyse the relationship between physical activity levels and mental health conditions in 220 students of Al-Islam Krian High School with an age range of 17 to 19 years, consisting of 70 male students (30%) and 150 female students (70%). This research design uses quantitative descriptive method through observation. The instruments used were the International Physical Activity Questionnaire Short Form (IPAQ SF) to measure physical activity levels and the Depression Anxiety Stress Scale 21 (DASS 21) to assess stress, depression, and anxiety. The results showed that 10% of students had low physical activity, 59% were moderate, and 31% were high. Data were analysed using SPSS 29 with the significance results of stress (p = -0.067), depression (p = -0.044), and anxiety (p = -0.031). Based on correlational analysis, it was found that there was no significant relationship, but it was negative. This means that the higher the physical activity, the lower the levels of stress, depression, and anxiety. Physical activity does not directly play a role in mental health factors, but has a tendency to reduce stress, depression, and anxiety in adolescents.